Prevalence, Antimicrobial Susceptibility Pattern, and Associated Factors of Urinary Tract Infections among Pregnant and Nonpregnant Women at Public Health Facilities, Harar, Eastern Ethiopia: A Comparative Cross-Sectional Study - Degu Abate; Dadi Marami; Shiferaw Letta (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. Urinary tract infection is one of the most common health problems worldwide, afflicting many women in reproductive age, especially in developing countries. Increased risk of infection has been attributed to pregnancy and antimicrobial resistance. Objective. To compare the prevalence, antimicrobial susceptibility pattern of the bacteria and associated factors of urinary tract infections among pregnant and nonpregnant women attending public health facilities, Harar, Eastern Ethiopia. Methods. A health facility-based comparative cross-sectional study was conducted among 651 randomly selected women from public health facilities, Harar, Eastern Ethiopia, between February 2017 and December 2017. Pertinent data were collected through a face-to-face interview using a structured questionnaire. The midstream urine specimen was collected and cultured on cysteine-lactose-electrolyte-deficient agar and blood agar. Pure isolates were tested against the ten most prescribed antimicrobials using the Kirby-Bauer disk diffusion method. Data were entered and analysed using Statistical Program for Social Sciences version 21. A p value <0.05 was considered statistically significant. Results. The overall prevalence of significant bacteriuria was 23% (95% CI: 13.6, 26.8). The higher proportion of bacteria were isolated from pregnant women (14.1%) compared to nonpregnant women (8.9%). Escherichia coli (28.8%) and Streptococcus aureus (14.3%) were the most common isolates. E. coli was resistant to amoxicillin (83.3%), trimethoprim-sulfamethoxazole (78.6%), and ciprofloxacin (81%), whereas S. aureus was resistant to chloramphenicol (81%), erythromycin (81%), and amoxicillin (76.2%). Current symptoms, and history of catheterization increase the likelihood of urinary tract infections. Conclusion. Pregnant women were more likely infected with bacterial pathogens than nonpregnant women. Current symptoms, and catheterization increase the odds of urinary tract infections. More than half of the isolates were resistant to the commonly prescribed antimicrobials. Regular assessment of urinary tract infections and antimicrobial resistance are recommended to provide effective therapy and thereby prevent urinary tract complications.